Detection of a novel large fragment deletion in the alpha-globin gene cluster using the CNVplex technology - Xu, Jianfei; Hu, Liang; Wen, Lijuan; Cao, Xianzhen; Xu, Hongyan; Luo, Qi; Long, Yuhong; Ji, Tingyu; Sun, Lifang; Wei, Fengxiang (Frontiers in Genetics, 2025)
ObjectiveTo describe the characterization of a novel deletion causing α-thalassemia.MethodsThe proband was a 4-year-old boy who presented with abnormal hematological parameters identified during routine blood investigation conducted for a cold. Three common α-globin gene deletions, three mutations, and 17 mutations in the β-globin gene were detected using PCR-flow fluorescence hybridization. Next-generation sequencing (NGS) and CNVplex technologies were employed to identify potential rare pathogenic mutation types. The CNVplex technology leverages variations in the lengths of linkage sequences of differential sequences at the same locus to produce linkage products of varying lengths, thereby enabling the detection of multiple loci within the same system. The newly identified deletions were further validated using customized third-generation sequencing (TGS) and Sanger sequencing.ConclusionIn this study, hematological analysis indicated a potential diagnosis of thalassemia in the proband, characterized by typical microcytic hypodermic features. A novel 134-kb deletion in the α-globin gene cluster was identified in this proband using the CNVplex technology. This deletion encompasses the genes HBZ, HBM, HBA2, HBA1, and HBQ1. Furthermore, we confirmed the gene deletion through customized TGS testing and Sanger sequencing, allowing us to determine the size of the deletion. The results suggest that this represents a new deletion of 146 kb that has not been previously reported, and we hypothesize that this deletion is likely the primary cause of the α-thalassemia trait observed in the proband.